2000
DOI: 10.1179/rer.2000.5.1.35
|View full text |Cite
|
Sign up to set email alerts
|

Blood parameters indicative of oxidative stress are associated with symptom expression in chronic fatigue syndrome

Abstract: Full blood counts, ESR, CRP, haematinics and markers for oxidative stress were measured for 33 patients diagnosed with chronic fatigue syndrome (CFS) and 27 age and sex matched controls. All participants also completed symptom questionnaires. CFS patients had increases in malondialdehyde (P <0.006), methaemoglobin (P <0.02), mean erythrocyte volume (P <0.02) and 2,3-diphosphoglycerate (P <0.04) compared with controls. Multiple regression analysis found methaemoglobin to be the principal component that differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
75
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 105 publications
(83 citation statements)
references
References 28 publications
7
75
1
Order By: Relevance
“…18 In particular, an enhanced activity of oxidative stress has been demonstrated in resting CFS patients and post-exercise. [18][19][20] Thus, impairment of mitochondrial oxidative phosphorylation and antioxidant defences have been implicated in the pathogenesis of CFS. 18;21 In the current study, differences were observed in the expression of HSP27 by CFS patients compared with control subjects, both in basal expression and following strenuous exercise.…”
Section: Discussionmentioning
confidence: 99%
“…18 In particular, an enhanced activity of oxidative stress has been demonstrated in resting CFS patients and post-exercise. [18][19][20] Thus, impairment of mitochondrial oxidative phosphorylation and antioxidant defences have been implicated in the pathogenesis of CFS. 18;21 In the current study, differences were observed in the expression of HSP27 by CFS patients compared with control subjects, both in basal expression and following strenuous exercise.…”
Section: Discussionmentioning
confidence: 99%
“…This increases inner membrane leakiness and lowers trans-membrane potential of the inner mitochondrial membrane (MIM), thus impairing mitochondrial function and production of ATP, resulting in reduced physical and mental performance with aging and disease [20] [24]- [26]. For example, chronic fatigue syndrome patients present with evidence of oxidative damage to DNA and lipids [26] [27], such as oxidized blood markers and oxidized membrane lipids that are indicative of excess oxidative stress [27] [28]. These patients also have sustained, elevated levels of peroxynitrite due to excess nitric oxide, which can also result in lipid peroxidation and loss of mitochondrial function as well as changes in cytokine levels that exert a positive feedback on nitric oxide production [29].…”
Section: Clinical Uses Of Membrane Lipid Replacement-fatiguementioning
confidence: 99%
“…Vitamin C is a potent antioxidant and acts as a cofactor for numerous biosynthetic and regulatory enzymes in the body [5] , which may account for its observed effects in this case. Oxidative stress has been implicated in chronic fatigue syndrome [11] and chemotherapy-related fatigue [12] . Parenteral vitamin C has been shown to decrease both cancer -and chemotherapyrelated fatigue in cancer patients [2] .…”
Section: Discussionmentioning
confidence: 99%